Visualizing Labour: Photographing the Factory Gates in May 1968. Issue 2 (July 2019) - Partridge, Benjamin
Abstract : This article examines the photographic depiction of factory gates during the strikes of May and June 1968 in France. These photographs form a distinctive subset of images of May 1968, offering a key visualization of the labour dispute and its relation to the broader political movement. Using research on images from newspapers, photojournalists collections and archival sources, it seeks to explore a facet of the visualization of 1968 often neglected in representations focused on street protest and university occupations in Paris, and situate these photographs in a broader historical context of images of the factory.